A comparative study of LiTi2(P8/9V1/9O4)3 and LiTi2(PO4)3: Synthesis, structure and electrochemical properties. (10th January 2018) - Pang, Jianyu; Kuang, Quan; Zhao, Yanming; Han, Wei; Fan, Qinghua
Abstract: NASICON-type LiTi2 (PO4 )3 (LTP) is a representative solid-state electrolyte and promising anode for rechargeable Li batteries. However, the electronic conductivity and specific capacity of LTP anode are encumbered by its massy and sluggish phosphate groups. Herein, vanadium (V) substitution compound LiTi2 (P8/9 V1/9 O4 )3 (LTPV) has been synthesized by using a selective vanadic source of Li3 VO4 at an adjusted sintering temperature of 700 °C. The PO4 3− radicals partly replaced by VO4 3− radicals are confirmed via XRD refinement, SEM, Raman and infrared spectra. The electronic conductivity of LTPV is two orders of magnitude higher than that of the undoped one, and meanwhile the charge-transfer impedance observably decreases after V substitution. More importantly, the V 5+ cations are electrochemical active in LTPV and contribute additional capacity during discharge and recharge processes. Benefitted from the increased electronic conductivity and the reduced charge-transfer impedance, the rate performance of LTPV is also distinctly improved when compared with the pristine LTP.